2014
DOI: 10.2319/121913-929.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of tooth movement and force magnitudes on the amount of tooth movement and root resorption in rats

Abstract: Objective: To investigate differences in the amount of tooth movement and root resorption that occurred after tipping and bodily movement of the maxillary first molar in rats. Materials and Methods: Ten-week-old female Wistar rats were divided into two groups according to type of tooth movement and subdivided into four subgroups according to the magnitude of applied force. Nickel-titanium closed-coil springs exerting forces of 10, 25, 50, or 100 g were applied to the maxillary left first molars to induce mesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 20 publications
2
37
1
4
Order By: Relevance
“…If application of higher forces does not increase the activity of inflammatory markers and the cascade of molecular and cellular events that follows, application of higher forces cannot increase the rate of tooth movement and can only expose the tooth to increased risk of side effects such as root resorption. Indeed, the experimental group that received 100 cN showed larger areas of root resorption in comparison with other groups (data not shown) in agreement with previous observations .…”
Section: Discussionsupporting
confidence: 92%
“…If application of higher forces does not increase the activity of inflammatory markers and the cascade of molecular and cellular events that follows, application of higher forces cannot increase the rate of tooth movement and can only expose the tooth to increased risk of side effects such as root resorption. Indeed, the experimental group that received 100 cN showed larger areas of root resorption in comparison with other groups (data not shown) in agreement with previous observations .…”
Section: Discussionsupporting
confidence: 92%
“…Many factors have been found to influence the orthodontic root resorption, including genetics [28], ethnicity [19], systemic diseases and allergic constitution [29], gender and age [7,30], treatment time [31], as well as the type (continuous or intermittent) and magnitude of orthodontic forces [32]. It has been found that heavy force used is associated with the prevalence of ARR [20], and an increase of force used is associated with the severity of ARR [33,34]. Intermittent force resulted in less ARR than continuous force [32,35] because the intermittent force provided cementum with the time to heal [36].…”
Section: Discussionmentioning
confidence: 99%
“…The orthodontic appliances used in this study were designed as described previously. 13 Orthodontic anchor miniscrews of 1.4 mm in diameter and 6 mm in length (Dual-top, Anchor Screw; Jeil Medical, Seoul, Republic of Korea) were placed into the anterior palatal bone with a hand screwdriver. Then, a 0.016-inchdiameter, round, cobalt-chromium wire (Elgiloy; Rocky Mountain Morita, Tokyo, Japan) was fixed over the occlusal surfaces of the left second and third molars, all right molars, and the orthodontic anchor screws with a self-curing resin (Super-Bond; Sun Medical, Shiga, Japan).…”
Section: Methodsmentioning
confidence: 99%